2022
DOI: 10.3390/s22103852
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Quantification of Adulterants in Fruit Juices Using Machine Learning Tools and Spectroscopy Data

Abstract: Fruit juice production is one of the most important sectors in the beverage industry, and its adulteration by adding cheaper juices is very common. This study presents a methodology based on the combination of machine learning models and near-infrared spectroscopy for the detection and quantification of juice-to-juice adulteration. We evaluated 100% squeezed apple, pineapple, and orange juices, which were adulterated with grape juice at different percentages (5%, 10%, 15%, 20%, 30%, 40%, and 50%). The spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…It should be noted that other authors, such as Mansour Rasekh et al, reported similar results, with superior performance of the SVM model compared to LDA, for the detection of adulterations in fruit juices using data from an electronic nose [ 38 ]. In contrast, other studies have reported better performance with SVM models compared to RF and LDA when using NIR spectroscopic data [ 28 ], while, using FT-IR data, SVM and LDA models outperform RF [ 13 ].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It should be noted that other authors, such as Mansour Rasekh et al, reported similar results, with superior performance of the SVM model compared to LDA, for the detection of adulterations in fruit juices using data from an electronic nose [ 38 ]. In contrast, other studies have reported better performance with SVM models compared to RF and LDA when using NIR spectroscopic data [ 28 ], while, using FT-IR data, SVM and LDA models outperform RF [ 13 ].…”
Section: Resultsmentioning
confidence: 93%
“…Support vector machines (SVM) and random forest (RF) models are notable examples of these techniques. Both SVM and RF can be applied for classification and regression purposes, and they have shown excellent results in the characterization of different fruit juices using different spectroscopic data [ 13 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of NIRS for fruit juice and wine authenticity has been confirmed in previous studies. For example, in the case of juices, Calle et al [57] achieved a detection limit of 5% when using a combination of NIRS and machine learning models to detect juice-to-juice adulteration of pineapple, apple, and orange juices with grape juice. Following that, an accuracy of up to 97.67% was obtained for their discrimination model (LDA and RF models), and their support vector regression (SVR) model achieved a prediction error of less than 1.7% for adulteration level [57].…”
Section: Infrared (Ir) Spectroscopic Techniquementioning
confidence: 99%
“…For example, in the case of juices, Calle et al [57] achieved a detection limit of 5% when using a combination of NIRS and machine learning models to detect juice-to-juice adulteration of pineapple, apple, and orange juices with grape juice. Following that, an accuracy of up to 97.67% was obtained for their discrimination model (LDA and RF models), and their support vector regression (SVR) model achieved a prediction error of less than 1.7% for adulteration level [57]. Shafiee et al [58] optimized data mining method on the NIR spectrum of lime juice to obtain the best classification result of 97% using support vector machine (SVM) method.…”
Section: Infrared (Ir) Spectroscopic Techniquementioning
confidence: 99%
See 1 more Smart Citation